M. QURAISH SHIHAB’S INTERPRETATION OF THE RELATIONSHIP BETWEEN MEN AND WOMEN IN TAFSIR AL-MISHBAH AND ITS RELEVANCE TO CHARACTER EDUCATION - Syahira, Sabila Azmi; Ghofur, Abdul; Sholeh Hasan, Muhammad (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. This study examines M. Quraish Shihab’s interpretation of seven gender-related Qur’anic verses in Tafsir al-Mishbah (QS. Al-Baqarah [2]: 187, 223, 228; Ali-Imran [3]: 36, 195; An-Nisa [4]: 34; Al-Hujurat [49]: 13). Employing a contextual-humanist hermeneutical approach, it examines the concepts of libas, harth, qawwamah, mubadalah, and atqakum as principles of equality (musawah), reciprocity, functional justice, and recognition of human potential based on piety rather than gender or social hierarchy. The research adopts a qualitative design, combining library study and thematic content analysis of Tafsir al-Mishbah, supported by recent empirical data on gender-based violence. Findings reveals that Shihab’s interpretation is progressive and moderate, rejecting literal-patriarchal readings that remain dominant in society. Nonetheless, a significant hermeneutical gap persists between the tafsir’s ideal vision and social realities, as reflected in the rise of 376,529 cases of gender-based violence against women in 2025 (an increase of 14.07%) and the persistence of school-related gender-based violence (SRGBV). The study concludes that Shihab’s perspective provides a strong foundation for a gender-responsive character education model integrating Thomas Lickona’s three pillars with critical awareness of patriarchal bias. Effective implementation requires contextualized curricula, gender-sensitive teacher training, and a school culture committed to equity and zero tolerance. Islamic education, thus, holds transformative potential in advancing a gender-just society consistent with Islam’s vision as rahmatan lil ‘alamin. Keywords: Quraish Shihab, tafsir al-mishbah, gender equality, gender-responsive, character education, Qur’anic hermeneutics, Abstrak. Artikel ini mengkaji penafsiran M. Quraish Shihab dalam Tafsir al-Mishbah terhadap tujuh ayat gender dalam Al-Qur’an, yaitu QS. Al-Baqarah [2]: 187, 223, 228; Ali-Imran [3]: 36, 195; An-Nisa [4]: 34; dan Al-Hujurat [49]: 13. Dengan menggunakan pendekatan hermeneutis kontekstual-humanis, penelitian ini menganalisis konsep libas, harth, qawwamah, mubadalah, dan atqakum sebagai prinsip kesetaraan esensial (musawah), kesalingan, keadilan fungsional, serta penghargaan terhadap potensi manusia yang berbasis ketakwaan, bukan jenis kelamin atau status sosial. Penelitian bersifat kualitatif dengan metode studi pustaka dan analisis konten tematik terhadap Tafsir al-Mishbah, didukung data empiris terkini mengenai kekerasan berbasis gender. Hasil kajian menunjukkan bahwa penafsiran Shihab bersifat progresif dan moderat, menolak pembacaan literal-patriarkal yang masih dominan di masyarakat. Namun, terdapat kesenjangan hermeneutis yang signifikan antara visi ideal tafsir dengan realitas sosial, sebagaimana tercermin dalam 376.529 kasus Kekerasan Berbasis Gender terhadap Perempuan (KBGtP) tahun 2025 (naik 14,07%) dan fenomena School-Related Gender-Based Violence (SRGBV) di lingkungan pendidikan. Artikel ini menyimpulkan bahwa penafsiran Shihab memiliki potensi besar sebagai landasan bagi model pendidikan karakter responsif gender yang mengintegrasikan tiga pilar Thomas Lickona dengan analisis kritis terhadap bias patriarkal. Implementasi yang efektif memerlukan kurikulum kontekstual, pelatihan guru yang sensitif gender, serta budaya sekolah berbasis zero-tolerance dan kesetaraan partisipasi. Dengan demikian, pendidikan Islam dapat berperan sebagai agen transformasi menuju masyarakat yang berkeadilan gender dan sesuai semangat Islam rahmatan lil ‘alamin. Kata kunci: Quraish Shihab, tafsir al-mishbah, kesetaraan gender, pendidikan, karakter responsif gender, hermeneutika al-Qur’an